Sexual counseling for people with acute coronary syndrome: educational video development - Laura Rizardi dos Santos Andrade; Lanay Dourado dos Anjos; Ana Paula Freitas Aguiar; Edvone Alves de Lima; Erika de Sá Vieira Abuchaim; Juliana de Lima Lopes; Camila Tákao Lopes; Vinicius Batista Santos (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to assess validity evidence of an educational video on safe sexual activity after acute coronary syndrome. Method: study in three phases: video development; content validity analysis by 11 experts; and analysis of validity based on response processes by seven people with coronary disease. The content validity ratio (CVR) was calculated with critical values for the second phase of 0.63 and for the third of 1.0. Results: the video addressed the importance of resuming sexual activity and positions that consume less energy, clinical warning signs, the importance of adhering to treatment and a welcoming environment for sexual practice. A CVR above the critical value was obtained with a total of 4 minutes and 41 seconds. Conclusion: the educational video brings together adequate content validity evidence and can be used as a tool for patients after acute coronary syndrome.